Growth and morphology of thermally assisted sinterable zirconia nanoparticle tribofilm. (November 2022) - Thrush, Steven J.; Comfort, Allen S.; Dusenbury, James S.; Nautiyal, Pranjal; Elinski, Meagan B.; Carpick, Robert W.; Demas, Nicholaos G.; Gould, Benjamin J.; Han, Xue; Wang, Xia; Qu, Hongwei; Barber, Gary C.
Abstract: Tribofilm formation mechanisms of a novel zirconia (ZrO2 ) nanoparticle antiwear additive were investigated. Spherical ZrO2 nanoparticles 5 nm in diameter with organic capping ligands were dispersed in a polyalphaolefin (PAO) synthetic base oil and tested between AISI 52100 steel counterfaces in a ball-on-disk tribometer under boundary lubrication contact conditions. Film formation was studied as a function of temperature, using PAO blends to maintain constant viscosity across the different temperatures. A temperature dependence was found, with higher temperatures assisting initial tribofilm growth and maintaining the steady-state tribofilm thickness. Findings are consistent with previous reports indicating the primary mechanism of tribofilm growth for zirconium oxide is nanoparticle capture at the sliding interface followed by particle accumulation and sintering.